Desenho de arquitetura para plataforma de serviço cloud : projeto para implementação de uma plataforma de serviço cloud em modelo PaaS - Aires, Sérgio Araújo (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management